The Falciform Ligament for Mesenteric and Portal Vein Reconstruction in Local Advanced Pancreatic Tumor: A Surgical Guide and Single-Center Experience. (1st October 2018) - Malinka, T.; Klein, F.; Denecke, T.; Pelzer, U.; Pratschke, J.; Bahra, M.
Abstract : Background . Since local tumor infiltration to the mesenteric-portal axis might represent a challenging assignment for curative intended resectability during pancreatic surgery, appropriate techniques for venous reconstruction are essential. In this study, we acknowledge the falciform ligament as a feasible and convenient substitute for mesenteric and portal vein reconstruction with high reliability and patency for local advanced pancreatic tumor. Methods . A retrospective single-center analysis. Between June 2017 and January 2018, a total of eleven consecutive patients underwent pancreatic resections with venous reconstruction using falciform ligament. Among them, venous resection was performed in nine cases by wedge and in two cases by full segment. Patency rates and perioperative details were reviewed. Results . Mean clamping time of the mesenteric-portal blood flow was 34 min, while perioperative mortality rate was 0%. By means of Duplex ultrasonography, nine patients were shown to be patent on the day of discharge, while two cases revealed an entire occlusion of the mesenteric-portal axis. Orthograde flow demonstrated a mean value of 34 cm/s. All patent grafts on discharge revealed persistent patency within various follow-up assessments. Conclusion . The falciform ligament appears to be a feasible and reliable autologous tissue for venous blood flow reconstruction with high postoperative patency. Especially the possibility of customizing graft dimensions to the individual needs based on local findings allows an optimal size matching of the conduit. The risk of stenosis and/or segmental occlusion may thus be further reduced.